Attention to carbon footprints in food choices and the crowding out effect of attention-leading nudges - Dominic Lemken; Daniele Asioli; Frederick Schoppa (Business Strategy and the Environment, 2024)
Consumer attention to carbon footprint labels may trigger efforts to adjust the agri-food sector toward more sustainable production. To assess attention levels, we used milk and bread products in an information display matrix (IDM), allowing consumers to direct attention or ignore various food product attributes. Our method improved upon previous IDM applications by introducing real-world complexity, featuring 25 attributes per product and multiple trade-offs. A randomizer ensured fairness by determining the order of attribute display. Results show that carbon footprints are not the primarily attended attributes. A salience nudge favoring carbon footprints directs attention to it but halves the attention paid to more holistic environmental footprints. We discuss strategies to promote environmental dimensions jointly and provide implications and recommendations for future labeling policies and marketing strategies.
Keywords: 330; choice-architecture; CO2-labels; consumer attention; eco-score; food choices; environmental score